Creatures : a novel - Van Meter, Crissy (Algonquin Books of Chapel Hill, 2020)
Set on a fictional island off the coast of Southern California, "Creatures" is a lyrical, inventive, and edgy literary debut in which a woman on the eve of her wedding must reckon with her chaotic but also free-spirited upbringing, her dysfunctional parents, and her attempts to love unconditionally as an adult despite never having been taught how.